2014
DOI: 10.1017/jse.2014.12
|View full text |Cite
|
Sign up to set email alerts
|

Are Teachers’ Beliefs Related to Their Preferences for ADHD Interventions? Comparing Teachers in the United States and New Zealand

Abstract: This investigation examined the relationship between teachers’ beliefs and their preferences for classroom interventions for behaviours consistent with attention-deficit/hyperactivity disorder (ADHD). Teacher ratings of intervention acceptability, effectiveness, and rate of change were compared across United States and New Zealand samples. Beliefs examined were personal teaching efficacy, general teaching efficacy, and pupil control ideology (PCI). Samples were compared regarding their preferences for the dail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…Almog and Shechtman (2007) showed that higher teacher efficacy is associated with more frequent use of positive-oriented CMSs. Another study, however, found no relationship between teacher efficacy and the preference for three specific CMSs for ADHD (Curtis et al 2014).…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Almog and Shechtman (2007) showed that higher teacher efficacy is associated with more frequent use of positive-oriented CMSs. Another study, however, found no relationship between teacher efficacy and the preference for three specific CMSs for ADHD (Curtis et al 2014).…”
Section: Introductionmentioning
confidence: 92%
“…In the present study, primary and secondary school teachers' reported frequency of use of CMSs was not related to teaching experience, knowledge about ADHD, teacher efficacy, or level of training in managing behavioral problems. Other studies also suggest that these factors play only a negligible or small role (Blotnicky-Gallant et al 2015;Curtis et al 2014;Hart et al 2017;Martinussen et al 2011;Murray et al 2011;Ohan et al 2008). Martinussen et al (2011), however, found a moderate association between the level of Canadian teachers' in-service training in ADHD and their reported frequency of use of instructional CMSs, but a weak relationship between training and the use of behavior management, suggesting that training is related to the frequency of use of some CMSs but not others.…”
Section: Teacher Characteristicsmentioning
confidence: 98%
“…Exhibiting and modeling positive attitudes also form positive and trusting relationships between teachers and pupils. In turn, the establishment of positive teacher-pupil relationships motivates those with SN to cooperate with their teachers and promotes academic motivation among all learners (Curtis et al, 2014). Although most preservice teachers support the notion of inclusion of pupils with SN, once they have completed their first year of active teaching most of them expressed significant negative attitudes toward inclusion (Boyle et al, 2013).…”
Section: The Role Of Teachers' and Peers' Attitudes In The Inclusion ...mentioning
confidence: 99%
“…Participant demographics. Basic demographic information was collected using an adaptation of the Background Information Questionnaire (BIQ; Curtis et al, 2014). Ritchie et al,2019).…”
Section: Methodsmentioning
confidence: 99%